Developing an in situ LED irradiation system for small-angle X-ray scattering at B21, Diamond Light Source - Beatrice E. Jones; Ann Fitzpatrick; Kieran Fowell; Charlotte J. C. Edwards-Gayle; Nikul Khunti; Katsuaki Inoue; Steven Daniels; Eugene Williams; Camille Blayo; Rachel C. Evans; Nathan Cowieson (Journal of Synchrotron Radiation, 2024)
Beamline B21 at the Diamond Light Source synchrotron in the UK is a small-angle X-ray scattering (SAXS) beamline that specializes in high-throughput measurements via automated sample delivery systems. A system has been developed whereby a sample can be illuminated by a focused beam of light coincident with the X-ray beam. The system is compatible with the highly automated sample delivery system at the beamline and allows a beamline user to select a light source from a broad range of wavelengths across the UV and visible spectrum and to control the timing and duration of the light pulse with respect to the X-ray exposure of the SAXS measurement. The intensity of the light source has been characterized across the wavelength range enabling experiments where a quantitative measure of dose is important. Finally, the utility of the system is demonstrated via measurement of several light-responsive samples.